2020
DOI: 10.1101/2020.07.24.215160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRANsCre-DIONE transdifferentiates scar-forming reactive astrocytes into functional motor neurons

Abstract: SUMMARYIn spinal cord injury (SCI), the scar-forming reactive astrocytes with upregulated GFAP proliferate aberrantly near the injury site, allowing themselves as a prime target for transdifferentiation into neurons to replenish dead neurons. However, the conventional use of GFAP promoter to target reactive astrocytes has two inherent problems: inadvertent conversion of normal astrocytes and low efficiency due to progressive weakening of promoter activity during transdifferentiation. Here, we report that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…LCN2 has been reported as an autocrine factor for reactive astrocytosis (Lee et al, 2009), has a neurotoxicity, and can be secreted from GFAP + reactive astrocytes in neurodegenerative disease animal model (Bi et al, 2013). Additionally, severe reactive astrocytes recognized by co-expression of LCN2 and GFAP were characterized as scar-forming reactive astrocytes in spinal cord injury animal model (An et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…LCN2 has been reported as an autocrine factor for reactive astrocytosis (Lee et al, 2009), has a neurotoxicity, and can be secreted from GFAP + reactive astrocytes in neurodegenerative disease animal model (Bi et al, 2013). Additionally, severe reactive astrocytes recognized by co-expression of LCN2 and GFAP were characterized as scar-forming reactive astrocytes in spinal cord injury animal model (An et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Custom-built video-rate laser-scanning confocal and two-photon microscope system previously implemented (Ahn, Kong et al, 2019, Ahn, Choe et al, 2017, Choe, Hwang et al, 2013, Lee, Kong et al, 2020, Park, Choe et al, 2018, Park, Kim et al, 2019, Seo, Hwang et al, 2015) was used. Four continuous-wave laser modules with output wavelengths at 405nm (OBIS 405, Coherent), 488 nm (MLD488, Cobolt), 561 nm (Jive, Cobolt) and 640 nm (MLD640, Cobolt) were used as an excitation sources for confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…A complementary intriguing option that is recently coming to the spotlight is to restore lost functions by exploiting the potential of the astrocytes to trans-differentiate into neurons. In particular, it has been shown that forced expression of selected transcription factors can transform astrocytes into glutamatergic [240][241][242][243][244], GABAergic [243,245,246], dopaminergic [247], retinal [248,249], and motor neurons [250] in mice. Intriguingly, astrocyte trans-differentiation into neurons can be achieved also by downregulating the expression of the polypyrimidine tract binding protein 1 gene (Ptbp1) by either a short hairpin RNA [251] or by expression of an ortholog of CRISPR-Cas13d (CasRx) and two suitable guide RNAs [252].…”
Section: Astrocyte Role In Adult Neurogenesis and As Neuronal Precursorsmentioning
confidence: 99%